Orchestrating Supply Chain Opportunities: Achieving Stretch Goals Efficiently - Zelikovsky, Alex (Business Expert Press, 2011)
Ebook from IG Library ; Efficient planning and superior execution against clear objectives is the way companies operate best. For many companies, the planning process is carefully orchestrated, objectives are set, budgets are negotiated, resources are allocated, and then it's up to the organization to execute. But what happens when the unexpected occurs? Say, an event occurs that throws the status quo into turmoil. What if your business declines by 40% in 1 month, what do you do? Conversely, what if your demand spikes by 50% in just a few months, what then? Suppose a natural disaster happens, or a new technology creates a significant, but unplanned opportunity? The authors call these events 'stretch opportunities'. This book will focus on strategic thinking and tactical examples of how best to prepare for such events. They outline common themes across all such challenges, and also introduce three key management concepts: Flexibility, Agility and Real Options. They also include a specific chapter on how to structure supply chains to capitalize on stretch opportunities and we provide specific tactical frameworks to build in agility, flexibility and real options into a supply chain. Finally, the authors end the book with a checklist that managers can use to ensure that the right questions are asked in developing supply chains so that the ability to "surge" at profitable opportunities is nourished.